Creating Awareness of Publications through Marketing: Case Study of DESIDOC Journal of Library & Information Technology (DJLIT) - Bansal, Alka (DESIDOC Journal of Library & Information Technology, 2016)
Marketing is not all about selling or making profit. It is a mix of pricing, promotion, development of markets, selling as well as distribution and one most important term that has been added in recently is after sales service and most successful marketing is considered to have a feedback mechanism. Feedback, not for the sake of getting the feedback, but careful analysis of the requirements of the clients, analysis of the feedback and then taking appropriate action on that. Marketing is all about creating awareness, making the customer delight and satisfaction with product/service. It is true for all be it design, product development, or service. Defence Scientific Information & Documentation Centre (DESIDOC), on behalf of DRDO brings out a journal—DESIDOC Journal of Library & Information Technology (DJLIT). It is a well known journal in the field of Library & Information Science. DESIDOC has taken certain initiatives for DJLIT in terms of tools and techniques applied for online and offline marketing of the Journal. The study points out the initiatives taken for marketing of the Journal for its all stakeholders and plans for the future. The study has provided some recommendations also. The article will help the LIS professionals to explore various forums to market their products and services. http://dx.doi.org/10.14429/djlit.36.2.9714